Hellenistic and Roman fine wares from the Byzantine contexts in Tyana/Kemerhisar (south Cappadocia) - Mondin, Cristina (Rei Cretariae Romanae Fautorum Acta, 2015)
In 2005 the Ancient Topography section of the University of Padua began a series of investigations on the northern slopes of the höyük at Kemerhisar, the ancient Tyana. The oldest structures brought to light during the course of this research were a Christian complex together with a series of shops leaning against it, dating from the late Roman/early Byzantine period. Both the Christian buildings and the shops were extensively damaged by subsequent settlements, particularly during the Seljuk and Ottoman periods.